Absorption characteristics of epidural levobupivacaine with adrenaline and clonidine in children. Issue 1 (20th November 2012) - Chalkiadis, George A.; Abdullah, Farah; Bjorksten, Andrew R.; Clarke, Alexander; Cortinez, Luis I.; Udayasiri, Sonal; Anderson, Brian J.; Lonnqvist, Arne
Summary Aim To determine if the addition of adrenaline, clonidine, or their combination altered the pharmacokinetic profile of levobupivacaine administered via the caudal epidural route in children. Methods Children aged <18 years old scheduled to undergo sub‐umbilical surgery were administered caudal levobupivacaine plain 2.5 mg·ml−1 or with adjuvants adrenaline 5 mcg·ml−1 or clonidine 2 mcg·ml−1 or their combination. Covariate analysis included weight and postnatal age (PNA). Time–concentration profile analysis was undertaken using nonlinear mixed effects models. A one‐compartment linear disposition model with first‐order input and first‐order elimination was used to describe the data. The effect of either clonidine or adrenaline on absorption was investigated using a scaling parameter (FabsCLON, FabsADR) applied to the absorption half‐life (Tabs). Results There were 240 children (median weight 11.0, range 1.9–56.1 kg; median postnatal age 16.7, range 0.6–167.6 months). Absorption of levobupivacaine was faster when mixed with clonidine (FabsCLON 0.60; 95%CI 0.44, 0.83) but slower when mixed with adrenaline (FabsADR 2.12; 95%CI 1.45, 3.08). The addition of adrenaline to levobupivacaine resulted in a bifid absorption pattern. While initial absorption was unchanged (Tabs 0.15 h 95%CI 0.12, 0.18 h), there was a late absorption peak characterized by a TabsLATE 2.34 h (95%CI 1.44, 4.97 h). The additional use of clonidine with adrenaline had minimal effect on the bifid absorption profile observed with adrenaline alone. Neither clonidine nor adrenaline had any effect on clearance. The population parameter estimate for volume of distribution was 157 l 70 kg−1. Clearance was 6.5 l·h−1 70 kg−1 at 1‐month PNA and increased with a maturation half‐time of 1.6 months to reach 90% of the mature value (18.5 l·h−1 70 kg−1) by 5 months PNA. Conclusions The addition of adrenaline decreases the rate of levobupivacaine systemic absorption, reducing peak concentration by half. Levobupivacaine concentrations with adrenaline adjuvant were reduced compared to plain levobupivacaine for up to 3.5 hours. Clonidine as an adjuvant results in faster systemic absorption of levobupivacaine and similar concentration time profile to levobupivacaine alone. Adding adrenaline with clonidine does not alter the concentration profile observed with adrenaline alone.